Special minimum income program: effects on improvement of the living conditions of the municipality of Mato Grosso, Paraíba, Brazil (Emancipação, 2020)
This paper aims to evaluate the progress made by the Special Minimum Income Program of the municipality of Mato Grosso, Paraíba State, from 2000 to 2010, as a public action to combat poverty. Developed since 2000 to alleviate the population’s poverty, the program consists of income transfer conditional on the beneficiaries counterparts in the areas of health and education. There was discussion about social policies in the international context, to understand the peculiarities of the Brazilian reality and the municipality of Mato Grosso/PB. From 2000 to 2010, Mato Grosso increased by 483.33% the number of beneficiary families, reduced the percentage of poor from 57.48% to 35.09% and improved the HDI by 55.22%. Multidimensionalaspects involving poverty linked to conditionalities have made significant progress, such as reducing child mortality, increasing life expectancy and per capita income.
Keywords: Social Policies. Poverty. Social Indicators. Special Minimum Income Program. Municipality of Mato Grosso/PB.